Review on pharmacological and potential cosmeceutical values of centella asiatica (pegaga) / Aida Liyana Wasli, Wan Azman Wan Ismail and Muhammad Izzuddin Zamery - Wasli, Aida Liyana; Wan Ismail, Wan Azman; Zamery, Muhammad Izzuddin (Faculty of Pharmacy, 2022)
Centella asiatica or also known as pegaga in Malaysia is a herbaceous perennial plant that belongs to the family of Apiaceae. This plant had been used for decades for its medicinal properties and immense potential. The present study aimed to review the pharmacological and potential cosmeceutical values of Centella asiatica. This review was based on research articles, reports, clinical trials, in vitro and in vivo trials retrieved from electronic databases and limited to the publication from the year 2015 onward. It excluded any articles related to food processing and trials that combined with other types of plants. Among the database used were the US National Library of Medicine (PubMed), ScienceDirect, EMBASE, Frontiers, Elsevier and Google Scholar. The pharmacological actions of Centella asiatica were determined through the disease model and its pathological mechanisms or any major findings based on the trials conducted. These findings were then classified according to the cardiovascular system, neurological system, endocrine system and digestive system. In terms of cosmeceutical values, Centella asiatica has immense potential in demonstrating anti-aging, skin hydration, anti-acne, enhancement of skin regeneration and skin barrier properties. These properties are highly regarded in the skincare industry, and therefore, this review can be used as a reference in further development of naturally based products. The phytochemical constituents responsible for most therapeutic actions were madecassoside, madecassic acid, asiaticoside and asiatic acid. Anti-inflammatory and antioxidants properties were found to be the core mechanisms of Centella asiatica and covered most of the pathologies.